2021
DOI: 10.5603/fm.a2020.0050
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical investigation of rare upper limb neuropathies due to the Struthers’ ligament or arcade: a meta-analysis

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It has been noted that the UN moves easily within the arcade. In one study, the musculotendinous type was observed in 54.2% cases, purely tendinous in 38.5%, and purely muscular in 7.2% (Mizia et al, 2021). It typically extends from the MIMS to the medial head of triceps brachii with a variable distance from the medial epicondyle of the humerus (Caetano et al, 2017).…”
Section: Elbowmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that the UN moves easily within the arcade. In one study, the musculotendinous type was observed in 54.2% cases, purely tendinous in 38.5%, and purely muscular in 7.2% (Mizia et al, 2021). It typically extends from the MIMS to the medial head of triceps brachii with a variable distance from the medial epicondyle of the humerus (Caetano et al, 2017).…”
Section: Elbowmentioning
confidence: 99%
“…Regardless of its character, it is questionable whether this structure can be a primary cause of the entrapment. However, it is seriously considered as a risk factor of recurrent ulnar neuropathy as a result of the UN transposition (Mizia et al, 2021).…”
Section: Elbowmentioning
confidence: 99%
“…In a meta-analysis by Mizia et al, the overall estimated pooled prevalence of the ligament was 1.8% and was 52.6% for the arcade. 42 The presence of accessory muscles like the anconeus epitrochlearis muscle, thought to be a muscular execution of Osborne's ligament, is important because it can lead to nerve entrapment. It occurs in > 18% of the European population 43,44 (►Fig.…”
Section: Musculocutaneous Nervementioning
confidence: 99%
“…In a meta-analysis by Mizia et al, the overall estimated pooled prevalence of the ligament was 1.8% and was 52.6% for the arcade. 42 …”
Section: Ulnar Nervementioning
confidence: 99%
“…Struthers' arcade is a non-constant, morphologically variable tendinous or muscular tissue situated 6-10 cm proximal to the medial epicondyle (ME), between the medial head of the triceps brachii muscle and MIS (1). Mizia et al (8) estimated its prevalence as 53%. Tubbs et al (9) described three types of Struthers' arcade.…”
Section: Anatomymentioning
confidence: 99%